LncRNA PCFL promotes cardiac fibrosis via miR-378/GRB2 pathway following myocardial infarction. (August 2019) - Sun, Fei; Zhuang, Yuting; Zhu, Haixia; Wu, Hao; Li, Danyang; Zhan, Linfeng; Yang, Wanqi; Yuan, Yin; Xie, Yilin; Yang, Shuang; Luo, Shenjian; Jiang, Wenmei; et al.
Abstract: Long noncoding RNAs (lncRNAs) are a class of novel molecular regulators in cardiac development and diseases. However, the role of specific lncRNAs in cardiac fibrosis remains to be fully explored. The aim of the present study was to investigate the effects and underlying mechanisms of lncRNA PCFL (pro-cardiac fibrotic lncRNA) on cardiac fibrosis after myocardial infarction (MI). Cardiac fibroblasts (CFs) with gain and loss of function of PCFL and mice with global knockout or overexpression of PCFL were used to explore the effects of PCFL on cardiac fibrosis. The data showed that PCFL was significantly increased in hearts of mice subjected to MI and CFs treated with transforming growth factor-β1 (TGF-β1). Overexpression of PCFL promoted collagen production and CF proliferation, while silencing PCFL exhibited the opposite effects. Compared with wild type MI mice, heterozygous knockout of PCFL (PCFL +/− ) in mice significantly improved heart function and reduced cardiac fibrosis after MI. While overexpression of PCFL impaired cardiac function and aggravated MI-induced cardiac fibrosis. The mechanistic data demonstrated that PCFL functioned as a sponge of miR-378. Luciferase reporter assay confirmed the interaction of PCFL with miR-378. MiR-378 inhibited collagen production by suppressing its target gene, GRB2 (growth factor receptor bound protein 2). Knockdown of PCFL led to an increase of miR-378. Silencing of miR-378 reserved the inhibitory effects of PCFL knockdown on collagen production, cell proliferation and GRB2 expression. In conclusion, the study identifies a novel pro-fibrotic lncRNA, PCFL, and the mechanism involves the direct interaction of PCFL with miR-378, which in turn relieves the inhibition effect of miR-378 on GRB2 and promotes cardiac fibrosis.